'Between the bridge and the brook': suicide and salvation in England c.1550–1650. Issue 3 (9th July 2014) - Hunter, Elizabeth K.
Abstract : That suicide was a damnable sin in Reformation England has been emphasized so far in the historiography of self-killing, but in practice the clergy were equivocal over the question of whether all self-killers were damned. This article re-examines English Protestant beliefs about suicide and salvation from the mid-sixteenth to the mid-seventeenth century. It suggests that clerical statements about the damnableness of suicide need to be understood in the context of the threat posed by Stoic philosophy. Religious writers rejected the notion of noble suicide and reiterated Augustinian theology that premeditated self-killing was a form of murder. However, the harsh rhetoric was mitigated by a number of factors that brought into question the idea that all suicides were destined for Hell. These included changing medical opinion about mental states, evidence of the good character of many suicides, belief in the overpowering influence of demonic forces and basic Christian charity and compassion.